WORD FORMATION PROCESSES OF SLANG IN DEADPOOL 2 MOVIE - Samperinding, Timorinda; Arifin, M. Bahri; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This research discusses about word formation process of English slang words and the functions of slang found in a movie. The data from this research were taken from Deadpool 2 movie script and in conducting this research, the researcher used two main theories to answer the research questions. They were theory of word formation processes by George Yule (2010) which aims to find how the slang words are formed in Deadpool 2 movie and theory about functions of slang proposed by Yanchun & Yanhong (2013). The methodology was descriptive qualitative research because it was relying on words as its data produced by the characters in Deadpool 2 movie and the data were explicated descriptively. All the data that have been collected in this research were analyzed through several stages namely, determining the part of speech, identifying the morphological unit, categorizing and analyzing the slang using word formation process by Yule’s theory. The analysis revealed that the word formation process of slang in Deadpool 2 movie consist of compounding, blending, acronym, clipping and multiple processes. Meanwhile, regarding the functions of slang, there are two functions appeared in Deadpool 2 movie, those are achieving politeness in order to show affectionate and emotive feeling as helps to convey their emotions.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//